2001
DOI: 10.1046/j.1440-1797.2001.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and management of hyperparathyroidism in end‐stage renal disease and after renal transplantation

Abstract: SUMMARY: Secondary hyperparathyroidism is an adaptive response to progressive loss of renal function so as to maintain calcium and phosphate homeostasis, 1,25‐dihydroxyvitamin D3 levels and normal bone turnover, despite skeletal resistance to parathyroid hormone. As feedback regulation fails, complications of parathyroid overactivity develop, and by the commencement of dialysis abnormal bone histology is present in almost all patients, with hyperparathyroid changes most commonly found. Post transplantation, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
(102 reference statements)
0
0
1
Order By: Relevance
“…We were unable to confirm the effect of secondary hyperparathyroidism and alveolar bone loss observed in adult patients with CRF [22]. In other studies of secondary hyperparathyroidism and bone disease, parathyroid hormone levels seven times higher than the normal upper range [23] have been observed. In this study, 57% of children with CRF had secondary hyperparathyroidism, which revealed a direct relationship between the history of secondary hyperparathyroidism and the signs of osteopenia in children with CRF as determined by the loss of lamina dura and alveolar bone lytic areas.…”
Section: Discussioncontrasting
confidence: 72%
“…We were unable to confirm the effect of secondary hyperparathyroidism and alveolar bone loss observed in adult patients with CRF [22]. In other studies of secondary hyperparathyroidism and bone disease, parathyroid hormone levels seven times higher than the normal upper range [23] have been observed. In this study, 57% of children with CRF had secondary hyperparathyroidism, which revealed a direct relationship between the history of secondary hyperparathyroidism and the signs of osteopenia in children with CRF as determined by the loss of lamina dura and alveolar bone lytic areas.…”
Section: Discussioncontrasting
confidence: 72%